PARTISIPASI POLITIK MASYARAKAT DALAM PEMILIHAN GUBERNUR DAN WAKIL GUBERNUR KALIMANTAN TENGAH TAHUN 2020 DI KECAMATAN BUKIT BATU KOTA PALANGKA RAYA - Wijoko Lestariono; Alfrid Sentosa (Jurusan Ilmu Pemerintahan, 2022)
The purpose of this study is to examine the politicalparticipation of the people in the Bukit Batu sub-district, thefactors that influence the political participation of the peoplein the Bukit Batu district in the 2020 election of governor anddeputy governor of Central Kalimantan, and the City ofPalangkaraya in increasing public political participation.the political participation of the KPU people. The methodused is a qualitative survey method used. Descriptivemethods and inductive approaches to explore andunderstand the meaning of research subjects learn from theproblems they face (Sugishirono, 2018). Data acquisitiontechnology Conducted through interviews, documentation,observations from primary data sources, Secondary sourcescontain sources identified through the targeted sample:Head of KPU Palangka Raya City (1 person), Head ofTechnical Sub-section for Palangka Raya City Election (1person), Head of District PPK Bukit Batu (1 person), Headof PPS Kecamatan Bukit Batu (1 person), Panwascam BukitBatu (1 person), Camat Bukit Batu (1 person) and theCommunity (10 people). Data analysis techniques with datareduction, data presentation, and withdrawal conclusion.Using Miriam Budialjo's theory of political participation inBasic Political Science (2008), the author analyzes fouraspects of political participation: socialization,participation in general meetings, participation in elections,and voting problems. The author finds that there are effortsto increase public political participation in Bukit BatuDistrict, Palangka Raya City with the efforts of the KPU inthe form of socializing political knowledge to the communitymore actively so that people use their voting rights in thefuture period. Conclusion The process of implementingpolitical participation in the Bukit Batu District communitydid not participate in the election due to the COVID-19pandemic situation, personal activities, lack of politicalunderstanding.